PJMHS 2021
DOI: 10.53350/pjmhs2115102756
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy of Ondansetron Pre-treatment in Alleviating Pain due to Propofol during General Anaesthesia with Placebo

Abstract: Background: Ondansetron is a 5HT3 receptor blocker and has multifaceted action like sodium channel blocker and µ - opioid agonist. Objective: To compare the efficiency of ondansetron pre-treatment in alleviating pain caused by propofol during induction of general anaesthesia with placebo. Material & Method: In this randomized controlled trail 120 patients of ASA grade I & II undergoing elective surgery were included and divided into two equal groups A & B by using lottery method. Each group compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The full-text screening was performed on 35 studies. Finally, 23 studies were included in the qualitative analysis, [11,13,[16][17][18][19][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] of which 20 studies were included in the quantitative analysis. [11,13,[16][17][18][19][23][24][25][26][27][28][29][30][31][32][33][34][35][36] The study selection procedure is shown in Figure 1 by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement flow chart.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full-text screening was performed on 35 studies. Finally, 23 studies were included in the qualitative analysis, [11,13,[16][17][18][19][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] of which 20 studies were included in the quantitative analysis. [11,13,[16][17][18][19][23][24][25][26][27][28][29][30][31][32][33][34][35][36] The study selection procedure is shown in Figure 1 by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement flow chart.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…A recent trial with 120 participants by Zahra et al [ 38 ] showed that ondansetron significantly reduced pain compared to placebo. Also, Powell et al [ 37 ] reported that pretreatment with 8 mg ondansetron decreased the post-anesthetic shivering incidence in adults without affecting temperature distribution during general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation